Exploration of the factors influencing parental decisions to allow their children to participate in clinical trials in paediatric infectious diseases. (4th April 2011) - Douglas, S J; Casey, M; Liossi, C; Faust, S N
Abstract : Aims: To explore the reasons behind parental decisions about participation of their children in specific paediatric infection clinical research scenarios in order to improve recruitment strategies. Methods: Parents of children aged 0–10 years were asked to complete a 20-page researcher-assisted semi-quantitative semi-structured questionnaire while waiting for their child's appointment in the outpatient waiting area. Socio-demographic information was collected. Open-ended and closed questions based on seven hypothetical paediatric clinical research scenarios were asked to explore reasoning behind the parental decision-making process. Qualitative and quantitative methods were used in the analysis. Results: 50 out of 62 approached parents (89%) completed the questionnaire, which took 10–25 min to complete. The overall parental opinion of paediatric clinical research was positive (55% positive, 45% indifferent, 0% negative). Most parents believed paediatric clinical research was helpful (64%), beneficial to all children (70%) and a way to give some sick children better medical treatment (58%). Of the hypothetical research scenarios, the observational studies showed the highest number of parents consenting (nasal swabbing 82%, blood sampling 74%), followed by PICU trials (low-dose steroid 49%, new unknown drug 25%). Vaccine studies had the lowest potential consent (new vaccine 12%, all-in-one vaccine trial 11%, all-in-one vaccine study 6%). The main incentive stated for hypothetical parental consent was the possible direct benefits of research to the child. The main barriers identified in potential refusal of parental consent were perceived risks outweighing the benefits of research, invasive procedures and a negative effect of participation on the child. Conclusions: When asked, the majority of parents have a positive opinion of paediatric clinical research. A parent's decision to consent for their child's participation in paediatric clinical research depends on a balance between the perceived risks and benefits of research. Minimising the main barriers to parental consent in future designs of paediatric clinical research could benefit recruitment rates. A large proportion of parents have a negative perception of vaccine research, highlighting the need for continued public education on the importance and safety of vaccines.